2005
DOI: 10.1037/1528-3542.5.4.408
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Stimuli, Divided Attention, and Memory.

Abstract: The emotion-memory literature has shown that negative emotional arousal enhances memory. S. A. Christianson (1992) proposed that preattentive processing could account for this emotion-memory relationship. Two experiments were conducted to test Christianson's theory. In Experiment 1, participants were exposed to neutral and negative arousing slides. In Experiment 2, participants were exposed to neutral, negative arousing, and positive arousing slides. In both experiments, the aforementioned variable was factori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
71
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 64 publications
(120 reference statements)
13
71
0
3
Order By: Relevance
“…This could possibly occur due to a form of the Pollyanna Principle where unconscious biases toward the positive may allow short-term reductions in retrieval due to alexithymia to be mitigated after longer retention intervals. Finally, it should be noted that emotionally enhanced memory in the general population is more typically seen with negative stimuli than with positive stimuli (e.g., Kern, Libkuman, Otani, & Holmes, 2005), such that some have concluded that negative emotion is stronger than positive emotion in multiple domains (Rozin & Royzman, 2001). As such, it is very possible that positive stimuli are simply less likely than negative stimuli to interact with alexithymia to alter memory.…”
Section: Discussionmentioning
confidence: 99%
“…This could possibly occur due to a form of the Pollyanna Principle where unconscious biases toward the positive may allow short-term reductions in retrieval due to alexithymia to be mitigated after longer retention intervals. Finally, it should be noted that emotionally enhanced memory in the general population is more typically seen with negative stimuli than with positive stimuli (e.g., Kern, Libkuman, Otani, & Holmes, 2005), such that some have concluded that negative emotion is stronger than positive emotion in multiple domains (Rozin & Royzman, 2001). As such, it is very possible that positive stimuli are simply less likely than negative stimuli to interact with alexithymia to alter memory.…”
Section: Discussionmentioning
confidence: 99%
“…A retenção de informações centrais da fase 2, no entanto, foi significativamente maior do que para a fase 1, o que também torna os dados consistentes com a literatura, visto que há um aumento do índice de recordação para informações centrais associadas com uma situação emocionalmente carregada (Kern, Libkuman, Otani & Holmes, 2005).…”
Section: Discussionunclassified
“…Indeed, Talmi et al (2007; see also Clark-Foos & Marsh, 2008;Kern, Libkuman, Otani, & Holmes, 2005) reported a study in which participants studied positive, neutral, and negative pictures under full or divided attention during encoding (i.e., a tone discrimination task). Although recall results revealed EEM under both full and divided attention for positive and negative pictures, there was a significant cost to memory performance for positive but not for negative stimuli when the stimuli were encoded under divided attention.…”
Section: Divided Attention During Encoding Of Emotional Stimulimentioning
confidence: 99%